IMPLEMENTATION OF THE LOCAL REGULATION NO. 13 YEAR 2010 CONCERNING MANAGEMENT OF DISASTER PREVENTION IN FLOOD EMERGENCY RESPONSE PHASE ON MANGKANG WETAN VILLAGE, TUGU SUB-DISTRICT, SEMARANG CITY - Darmantuah P Gultom; Zainal Hidayat (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
Disaster is an apprehensive incident to everyone. When it happens, emergency response of disaster is needed to be done due to minimize and rescue victims and material disadvantage. Semarang has some district where usually affected by disaster, of them that is concerned is Mangkang Wetan Village, Tugu Sub-District, Semarang City, flooding disaster potentially region every year. Through Province Regulation Semarang City. Through the Local Regulation No. 13 year 2010 concerning Management of Disaster Prevention, committed consistently to fulfil with responsibility protecting the people. The matter should be solved and settled is what is implementation of the Local Regulation no. 13 year 2010. Objective of this thesis is to comprehend the implementation of the Local Regulation no. 13 year 2010 concerning Management of Disaster Prevention in Flood Emergency Response Phase on Mangkang Wetan Village, Tugu Sub-District, Semarang City and the obstacles on realize the implementation. Thesis used qualitative descriptive method with. Results of the thesis showed that The Local Regulation No. 13 year 2010 concerning Management of Disaster Prevention is well implemented, nevertheless there some actions aren’t done maximally. Some obstacle on fulfilling the implementation such budgeting, infrastructure access, and environmental issues. Some recommendation to resolve offered is BPBD coordination with relevant agencies to normalize Beringin River, extra budget provision for the disaster alert groups, supply of buoys replenishment, emergency boats, urgent equiments needed when flood occurs.